Emissão de gases de efeito estufa em sistemas de manejo em solo do planalto médio do Rio Grande do Sul - Escobar, Luisa Fernanda (2008)
Agriculture is directly linked to atmospheric concentration of greenhouse gases (GHG) through basic processes that occur in the soil-plant system. Agricultural soils can act as a source or sink of GHG depending on the management practices adopted. The objective of this research was to evaluate the GHG flux in different soil management systems. This project was constituted by two studies, conducted in long-term (22 years) experiment in a Rhodic Hapludox located in FUNDACEP research center, Cruz Alta, RS, Brazil. A study was conducted during 2006-2007 to evaluate the C-CO2 flux in a no-till soybean cropping system. Data were collected by an automatic meteorological station mounted in micrometeorological tower two meters above the ground. Turbulent variables were measured by a three-dimensional sonic anemometer Campbell-3D (wind and temperature components) and by an infrared gas analyzer Licor 7500 (H2O e CO2). Eddy covariance method was employed to measure the C-CO2 exchange that resulted of the interaction between atmosphere and the soybean cropping system. Soil temperature was measured using two sensors (thermopar) installed in the soil and for moisture measurement were used two sensors ECH2O. Results confirmed the high photosynthetic activity during daylight, with high values of C-CO2 influx. Low values of total C-CO2 influx were verified, with the culture responding to environmental conditions and to phenologic stage. Soybean cropping system liquid C-CO2 balance was estimated in -7,1 g C m-2. This result suggests a low soybean potential in increasing soil organic matter, even under no-till system. A second study was conducted during winter soil tillage operations (May 2007), using the closed camera method, to evaluate N2O, CH4 and CO2 flux in different soil management systems (conventional tillage, no-till system with soybean and maize residues). The analysis was made through gaseous chromatography. GHG emissions were affected by cropping system and were not affected by soil tillage. Highest N2O emissions occurred in the no-till system with soybean residues. The no-till system with maize residues had similar N2O emissions to conventional tillage system, this result was explained due to low nitrate soil content. The three systems evaluated acted as a CH4 sink. CO2 emissions were higher in the no-till system.